A quantitative model of amphetamine action on the 5‐HT transporter. (February 2014) - Sandtner, Walter; Schmid, Diethart; Schicker, Klaus; Gerstbrein, Klaus; Koenig, Xaver; Mayer, Felix P; Boehm, Stefan; Freissmuth, Michael; Sitte, Harald H
<x xml:space="preserve">Abstract</x> Background and Purpose Amphetamines bind to the plasmalemmal transporters for the monoamines dopamine (DAT), noradrenaline (NET) and 5‐HT (SERT); influx of amphetamine leads to efflux of substrates. Various models have been proposed to account for this amphetamine‐induced reverse transport in mechanistic terms. A most notable example is the molecular stent hypothesis, which posits a special amphetamine‐induced conformation that is not likely in alternative access models of transport. The current study was designed to evaluate the explanatory power of these models and the molecular stent hypothesis. Experimental Approach Xenopus laevis oocytes and HEK293 cells expressing human (h) SERT were voltage‐clamped and exposed to 5‐HT, p‐chloroamphetamine (pCA) or methylenedioxyamphetamine (MDMA). Key Results In contrast to the currents induced by 5‐HT, pCA‐triggered currents through SERT decayed slowly in Xenopus laevis oocytes once the agonist was removed (consistent with the molecular stent hypothesis). However, when SERT was expressed in HEK293 cells, currents induced by 3 or 100 μM pCA decayed 10 or 100 times faster, respectively, after pCA removal. Conclusions and Implications This discrepancy in decay rates is inconsistent with the molecular stent hypothesis. In contrast, a multistate version of the alternative access model accounts for all the observations and reproduces the kinetic parameters extracted from the electrophysiological recordings. A crucial feature that explains the action of amphetamines is their lipophilic nature, which allows for rapid diffusion through the membrane.